2002
DOI: 10.1002/ca.10011
|View full text |Cite
|
Sign up to set email alerts
|

Adipose body of the orbit

Abstract: The adipose body of the orbit (ABO) fills most of the orbital cavity, surrounding the eyeball, muscles, nerves, and vessels. It was studied in histologic section in the three basic planes in the fetus, neonate, and adult. In the retrobulbar area, that is, posterior to the eyeball, adipose tissue occupies the space around the optic nerve and penetrates between the recti muscles, describing a four-leafed clover pattern in frontal section. The fatty tissue of the retrobulbar area also includes the peripheral ring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 12 publications
0
12
1
Order By: Relevance
“…To date, there are no publications to suggest differences in fat tissue accumulation at the intraconal (posterior) and extraconal (anterior) sites. A publication by WolframGabel R et al found no septum between intra-and extraconal fat and histologic sections demonstrated that the adipose body of the orbit is a single anatomic entity (27). It was clear, however, from our work that in cultured fibroblasts, the degree of TPO mRNA expression was similar in the two groups.…”
Section: Discussioncontrasting
confidence: 53%
“…To date, there are no publications to suggest differences in fat tissue accumulation at the intraconal (posterior) and extraconal (anterior) sites. A publication by WolframGabel R et al found no septum between intra-and extraconal fat and histologic sections demonstrated that the adipose body of the orbit is a single anatomic entity (27). It was clear, however, from our work that in cultured fibroblasts, the degree of TPO mRNA expression was similar in the two groups.…”
Section: Discussioncontrasting
confidence: 53%
“…RAT is more developed in the parabulbar area, filling the space behind the eyeball. Orbital adipose tissue is limited by the peripheral muscle cone into a lattice-like structure, the margins of which consist of the four oculomotor muscles (superior, inferior, medial and lateral rectus muscles) which divide the adipose tissue into four sheets 19 . RAT histologically belongs to white (unilocular) fat tissue.…”
Section: Introductionmentioning
confidence: 99%
“…OF fills most of the orbital cavity, and surrounds the globe, extraocular muscles, nerves and vessels providing support to these delicate structures and protecting against sight-threatening mechanical and inflammatory trauma (Wolfram-Gabel & Kahn 2002). Two types of orbital adipose tissue have been defined: anterior OF consisting chiefly of small adipocytes that are separated by thick conjunctival septa providing support to intraorbital structures, and posterior OF consisting of larger adipocytes separated by thin conjunctival septa enabling structural movements within the orbit (Bremond-Gignac et al 2004).…”
Section: Introductionmentioning
confidence: 99%